Analisis Pengaruh Pengeluaran Pemerintah Sektor Pendidikan dan Sektor Kesehatan Terhadap Pertumbuhan Pendapatan Asli Daerah Serta Pertumbuhan Produk Domestik Bruto Sebagai Variabel Intervening (Studi Kasus Di Kota Mataram Nusa Tenggara Barat) - Mahmudi, Hadi; Manan, Abdul; Mustain, Mustain (Jurnal Ekonomi dan Bisnis, 2017)
This study aims to: examine the effect of Government Expenditures on education and health on the growth of Local Original Income in Mataram City through the growth of GRDP. This research uses quantitative approach with Path Analysis (Path Analysis) method. The data used is sourced from budget of 2008-2015 period at DinasPendidikan, Dinas Kesehatan and BPS of Mataram. The result of the research shows that 1. The education sector government expenditure (X1) has a positive and significant effect on the growth of PAD and on the growth of GRDP (Y1) has positive but not significant influence. 2. Health sector government spending has a negative and insignificant effect on PAD growth and on GRDP growth (Y1) has 5.1.5. GDP growth (Y1) has a negative effect on PAD growth but is not significant. 3. Education sector government expenditure (X1) on indirect growth of PAD through GDP growth has negative and insignificant effect. 4. Health sector government expenditure (X2) on indirect growth of PAD through GDP growth has a positive and insignificant effect